2014
DOI: 10.1073/pnas.1404448111
|View full text |Cite
|
Sign up to set email alerts
|

Economic scarcity alters the perception of race

Abstract: Significance Racial disparities on socioeconomic indices expand dramatically during economic recession. Although prior explanations for this phenomenon have focused on institutional causes, our research reveals that perceived scarcity influences people’s visual representations of race in a way that may promote discrimination. Across four studies, scarce conditions led perceivers to view Black people as “darker” and “more stereotypically Black” in appearance, relative to control conditions, and this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
191
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(208 citation statements)
references
References 28 publications
15
191
1
1
Order By: Relevance
“…Below we review each briefly. Researchers have used reverse correlation tasks to identify features diagnostic for Black and White faces (Fiset, Wagar, Tanaka, Gosselin, & Bub, 2007;Krosch & Amodio, 2014), Moroccan faces (Dotsch et al, 2008, Chinese faces (Dotsch et al, 2008), European and Australian (Imhoff, Dotsch, Bianchi, Banse, & Wigboldus, 2011), as depicted in Figure 4. Various studies have focused on visualising the gender of faces (see Figure 5; Mangini & Biederman, 2004;Nestor & Tarr, 2008;Dotsch et al, 2011) and of bodies (Johnson, Iida, & Tassinary, 2012;Lick, Carpinella, & Preciado, 2013).…”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…Below we review each briefly. Researchers have used reverse correlation tasks to identify features diagnostic for Black and White faces (Fiset, Wagar, Tanaka, Gosselin, & Bub, 2007;Krosch & Amodio, 2014), Moroccan faces (Dotsch et al, 2008, Chinese faces (Dotsch et al, 2008), European and Australian (Imhoff, Dotsch, Bianchi, Banse, & Wigboldus, 2011), as depicted in Figure 4. Various studies have focused on visualising the gender of faces (see Figure 5; Mangini & Biederman, 2004;Nestor & Tarr, 2008;Dotsch et al, 2011) and of bodies (Johnson, Iida, & Tassinary, 2012;Lick, Carpinella, & Preciado, 2013).…”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…For instance, preferential visual attention to the eyes of own-race (vs. other-race) individuals predicted own-race bias in face recognition such that people were better able to recognize people from their own race and more willing to interact with own-race over other-race members (Kawakami et al, 2014). Moreover, biased perception predicted disparities in resource allocation-specifically the perception of African Americans as "Blacker"-and was associated with less willingness to grant resources to this racial group (Krosch & Amodio, 2014). In a separate context, perceived physical proximity led highly identified group members (i.e., Yankees fans) to express more discriminatory attitudes toward members of a threatening outgroup (i.e., the Red Sox) and a preference for sitting farther away from them at a sporting event (Xiao, Wohl, & Van Bavel, 2016).…”
Section: Perceptual Model Of Intergroup Relationsmentioning
confidence: 99%
“…Some recent work has demonstrated that perception of "Blackness" in African Americans was influenced by economic resource scarcity (Krosch & Amodio, 2014). These researchers presented people with pairs of degraded face images and had them choose the one that looked more "Black."…”
Section: Face Perceptionmentioning
confidence: 99%
See 2 more Smart Citations